Role of exfoliative cytology in oral lesions: with special reference to rule out malignancy - Singh, A (Journal of College of Medical Sciences-Nepal, 2010)
Oral malignancy is quite common in country like India because of tobacco chewing and smoking. Cytology is cheaper and easy procedure that can be carried out at outdoor patient department to diagnose malignancy at early stage. The present study carried out to detect cancer pre-invasive stage by use of exfoliative cytology and to explore the possibility of using this technique in diagnosis of other oral lesions considered as premalignant ones. A total 102 patients referred from OPD and surgery department of J.A. Group of Hospital, Madhav Dispensary and Cancer Hospital, Gwalior, between July 2004 to October 2005, were included in this study. Two smears by scrap method, from each patient were prepared and after air dried stained with RAPID PAP stain. The smear were evaluated along with clinical, epidemiological data and classified in group I to IV according to the Papanicolaou classification. In our result 25 cases were normal. 47 were Leukoplakia with mean age 47.5 years, 85% male. Smear show anucleated squames predominantly 53%. Six cases were submucous fibrosis 66.7% female with mean age 38.3 years and, smear revealed rarification of nuclei in 66% cases. Two cases of mucosal hyperemia (Erythema), one-one case of traumatic ulcer and granular buccal mucosa included. Out of Twenty cases of malignancy, male were 75% with mean age of 46 year. Cheek and tongue were the common site with incidence of 60%. The smear revealed inflammatory cells in 100%, malignant cells in 75% cases either in groups or in singles. The third type of cells 60%, the undifferentiated cells 37%, and Tadpole cells in 5% cases. In study 75% cases were positive for cancer, 10% were suspicious for cancer and remaining 15% were given as negative for cancer. Cytology is reliable diagnostic tool in diagnosis of presence or absence of malignancy in a lesion with high accuracy rate. The oral cytologic technique is easy to do and can provide the help of surgeon/physician, where he/she might hesitate to perform an invasive procedure, like a biopsy, or desire more information regarding a lesion before referring the patient. Key words: Cancer; exfoliative cytology; leukoplakia; oral malignancy. DOI: 10.3126/jcmsn.v6i2.3614 Journal of college of Medical Sciences-Nepal, 2010, Vol.6, No-2, 29-37